'You Can Touch But Do Not Read': The 'Future‐Rustic' Work of Kathryn Findlay. (4th April 2013) - Titman, Mark; Titman, Mark
Abstract 'By turns curvaceous, fluffy, leafy, green, soft and hairy', the work of Kathryn Findlay is palpably 'future‐rustic' in all its formal and material manifestations. Guest‐editor Mark Titman explains how Findlay's designs also more subtly respond 'to the richness of a given situation, the resources and natural conditions that each site and its surrounding context reveals', coming out of an approach that has been equally influenced by her rural childhood on a farm in Scotland as almost two decades of working in Japan.